2017
DOI: 10.1371/journal.pone.0178172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of verbal task complexity in a working memory paradigm in patients with type 1 diabetes. A fMRI study

Abstract: Type 1 diabetes (T1D) is commonly diagnosed in childhood and adolescence, and the developing brain has to cope with its deleterious effects. Although brain adaptation to the disease may not result in evident cognitive dysfunction, the effects of T1D on neurodevelopment could alter the pattern of BOLD fMRI activation. The aim of this study was to explore the neural BOLD activation pattern in patients with T1D versus that of healthy matched controls while performing two visuospatial working memory tasks, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 66 publications
4
10
0
Order By: Relevance
“…Key components of executive function, namely, working memory and response inhibition, have been addressed in multiple neuroimaging studies. Recent studies have found aberrant activation during working memory studies of individuals with type 1 diabetes relative to controls . In earlier studies, activation differences were found between those cohorts, and between individuals having type 1 diabetes with and without retinopathy, when glucose levels were clamped to hypoglycemic levels, but not, however, when the clamping was to euglycemic levels .…”
Section: Introductionmentioning
confidence: 95%
“…Key components of executive function, namely, working memory and response inhibition, have been addressed in multiple neuroimaging studies. Recent studies have found aberrant activation during working memory studies of individuals with type 1 diabetes relative to controls . In earlier studies, activation differences were found between those cohorts, and between individuals having type 1 diabetes with and without retinopathy, when glucose levels were clamped to hypoglycemic levels, but not, however, when the clamping was to euglycemic levels .…”
Section: Introductionmentioning
confidence: 95%
“…Besides, elevated HbA1c at diagnosis was found correlated with decreased volume in cerebellar white matter (33). Except for structure differences, some studies also found activation differences between T1DM and healthy controls in cerebellum (41,42).…”
Section: Discussionmentioning
confidence: 94%
“…The behavioral results are shown in more detail in our previous papers [32, 33]. In summary, the results showed that both groups had a high percentage of correct answers in tasks A and B (between 88.28% and 94.53% of correct answers).…”
Section: Resultsmentioning
confidence: 64%
“…Nevertheless, to our knowledge, there are no functional connectivity studies during WM tasks in this type of patient. Therefore, our goal was to evaluate brain connectivity during a visuospatial WM task in a sample of young adults with T1D, and we studied the brain activity pattern through f MRI related to this cognitive function [32, 33]. In these previous studies, T1D patients and the healthy control group showed activations expected by the task in areas of the lateral prefrontal cortex, anterior cingulate cortex and cerebellum, but T1D patients showed less cortical activations than the control group in the left parietal cortex, premotor cortex, and superior frontal gyrus and more intense activations than the controls in the inferior frontal gyrus, basal ganglia and cerebellum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation